A New Parcel-Cage Size and Tracking System: Effects on Transportation and Handling in a Logistics Company - Widroth, Linnéa (My University, 2021)
When transporting parcels via trucks, optimizing the loading capacity (load factor) is important for economic and environmental reasons. Accessibility to parcel-cages in the parcel process is important for the delivery to run as efficiently as possible. The load factor of the truck is underutilized with the current parcel-cage, thus there is potential to increase the load factor with a different solution. One track in this master’s thesis is to investigate how a new size of parcel-cage affects transport efficiency, ergonomics and time of handling cages. Another problem is the occurrence of long- and short-term shortages of cages in the process. A second track will therefore be to propose a new tracking system for the cages. A triangulation of methods: literature studies, quantitative studies and qualitative studies; was used in this project. Interviews, observations and statistical data gathering and analysis were used to define the current state of transportation and handling of the parcel-cages. For the new solution, a literature study and quantitative study were carried out for the two tracks, defining and evaluating the optimal cage size and proposing a new tracking system. A comparison between the current state and the new solutions was conducted. The optimal cage size was defined so that two cages could be stacked on top of each other, using bars inside the trucks. The new cage can potentially transport 39 % more parcels per pallet place than the current one, with regard to the average number of parcels transported in the different cages. The load factor in the truck increases by 44 % with the new cage. Packing parcels into cages was identified as the riskiest work task regarding physical ergonomics. The cages were divided into three zones depending on the lifting heights. The medium zone (from knee-level to shoulder height) is considered an acceptable lifting zone. The low and high zones are considered more ergonomically risky lifting heights. The study indicates that the new cage dimensions increase the number of acceptable lifts by 44 %, thanks to the difference in lifting heights. An evaluation of the physical loading for situations with different weight of parcel, posture and time was conducted. The combination of high-weight of parcels (>15 kg) with unsuitable lifting heights resulted in the riskiest situations. Since more cages are needed to transport the same volume of parcels, the time for handling the cages may increase by around 44 % for some work tasks. Cage shortages can be reduced by providing knowledge of how the cages are transported and the inventory levels at the terminals, to facilitate empty cage transportation. The study suggests that the cages can become more available with a passive UHF (Ultra high frequency) RFID (Radio-frequency identification) tracking system at cage-level. The findings indicate that transport efficiency and physical ergonomics can be improved with the new cage size, while the time required for handling cages may increase. The new tracking system could reduce the handling time with a more automatic system and reduction of work tasks in production.
Keywords: Parcel handling, Cage handling, Parcel-cage, Transport efficiency; Physical ergonomics, Tracking system.